EVALUASI REALISASI PANDUAN RANCANG KOTA KAWASAN CIKINI SUB KAWASAN 1 DAN 2 - Carina, Nina; Hartawidjaja, Elisha; Pricilia Angel R.M; Angrica, Kelly; Annisa Diva; Chen, Stephen (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The city of Jakarta as the National Capital is always growing and changing. To control and manage this the DKI Jakarta Provincial Government has a tool in the form of a-Urban Design Guidelines (UDGL) as stated in DKI Jakarta Provincial Governor Regulation number 147 of 2017 concerning Guidelines for Preparing Urban Design Guidelines. UDGL was prepared as a strategy to implement quality policies on urban design and urban architecture. UDGL guides urban design actors, including urban planning and design expertise, developers, private sectors, and other parties, to create a common perception and consistency with local governments. The large number of actors who play a role in the development of the city of Jakarta, as well as the very rapid changes in city development, are challenges in realizing physical development by the UDGL. The 2030 DKI Jakarta Provincial Spatial Planning Plan has designated the Cikini Area in Central Jakarta as one of the central system activities of the Central Jakarta Administrative City. As a guide, what is stated in the UDGL document can be implemented completely as stated, but it can also only be implemented partially. The evaluation of the City Design Guide for the Cikini Region Sub Regions 1 and 2 aims to assist the DKI Jakarta Provincial Government in seeing the suitability of the guideline with the implementation of the development that is taking place. By using descriptive-analytical-comparative methods, the research produced direct observation results in the field which were compared with the aspects contained in the UDGL and other supporting documents. The results of the study purposed to be a review to help the DKI Jakarta Provincial Government see the suitability of development to determine steps for the next UDGL.